Caesarean section delivery and its associated factors in Ghana: A multilevel analysis - Werkneh Melkie Tilahun; Mulat Belay Simegn; Alegntaw Abate; Eyasu Bamlaku Golla; Mohammed Ahmed Ali; Hawi Kumbi; Smegnew Gichew Wondie; Habtamu Geremew (PLoS ONE, 2025)
Background Even if the ideal rate for caesarean section (CS) is considered 10–15%, worldwide CS rates have been steadily increasing, without significant additional benefit to women’s health. Its overuse was associated with maternal and fetal complications. Therefore, this study aimed to determine the rate of CS delivery and associated factors among women delivered in health facilities in Ghana. Methods A cross-sectional study was conducted using the 2022 DHS datasets from Ghana. A total of 5231 weighted samples were included. STATA.16 was used for analysis. A multilevel logistic regression was applied. An adjusted odds ratio with a 95% CI and a p-value <  0.05 was used to declare significantly associated factors. Result The prevalence of CS in Ghana was 20.29% [95% CI = 19.23–21.41%]. Age 25-34 [AOR = 1.32, CI: 1.04, 1.68] and 35 + [AOR = 1.57, CI: 1.16, 2.11], primary [AOR = 1.58, CI: 1.21, 2.07], secondary [AOR = 1.36, CI: 1.07, 1.73], and higher [AOR = 2.24, CI: 1.58, 3.17] education, richer [AOR = 1.45, CI: 1.06, 1.99] and richest [AOR = 2.35, CI: 1.63, 3.39] wealth index, employment [AOR = 0.77, CI: 0.64, 0.92], primiparous [AOR = 1.33, CI: 1.07, 1.67], giving first birth after the age of 35 [AOR = 4.58, CI: 1.88, 11.19], multiple pregnancy [AOR = 5.53, CI: 4.02, 7.62], large birth size [AOR = 1.25, CI: 1.06, 1.48], 4–6 kg birth weight [AOR = 2.13, CI: 1.55, 2.92], as well as residing in Volta [AOR = 1.98, 95% CI: 1.22, 3.22] and Bono East [AOR = 2.02, 95% CI: 1.28, 3.19] regions were significant factors associated with CS delivery in Ghana. Conclusion The rate of CS was higher than previous studies in Ghana and the WHO recommended level, making it a public health concern. Age, education, wealth, employment, parity, age at first birth, pregnancy type, birth size, birth weight, and region were significantly associated with CS. Therefore, strategies aimed at examining guidelines for proper indications and uses of CS may lead to an improvement CS rate.